The Role of Forensic Auditors in Proving Corruption Cases - Rifki Rinaldi Ongi; Dian Ekawaty Ismai; Suwitno Yutye Imran (International Journal of Law, Crime and Justice, 2025)
This article aims to analyze the role of forensic auditors in the process of proving corruption crimes in Indonesia, as well as the quality of evidence produced by forensic auditors in supporting law enforcement. This study uses a normative legal approach with legislative analysis and a comparative approach. The results of the study indicate that forensic auditors play a very significant role in detecting, uncovering, and preventing corruption through investigative auditing. Forensic auditors are not only involved in the process of gathering evidence related to financial crimes but also serve as expert witnesses who provide strong evidence in court. The quality of evidence provided by forensic auditors depends on their professional competence and the application of systematic analysis techniques, as well as the importance of collaboration with other law enforcement agencies. There is a need for improved regulation, ongoing training, and closer synergy between forensic auditors and legal institutions to strengthen the eradication of corruption in Indonesia.